2021 IEEE Madrid PowerTech 2021
DOI: 10.1109/powertech46648.2021.9494784
|View full text |Cite
|
Sign up to set email alerts
|

A Techno-Economic Analysis of meshed Topologies of Offshore Wind HVAC Transmission

Abstract: This work develops a method of quantifying the effect of adding meshed connections to radial network topologies used for offshore extraction. The method accounts for Capital Expenditures (CAPEX), Corrective maintenance (CM), losses and Expected Energy Not Transmitted (EENT). The stochastic nature of wind is also accounted for. The method is applied to a statistically significant randomly generated population of Offshore Wind Power Plant (OWPP) pairs. Analysis of both Medium Voltage (MV) and High Voltage (HV) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…An architecture of a transmission line could deliver the generated energy but face a loss of power along the transmission line, and the delivered energy is slightly below the expected threshold. In other research by [81][82], topology degeneration also induced expected energy not transmitted (EENT).…”
Section: Degradation Valuementioning
confidence: 99%
See 1 more Smart Citation
“…An architecture of a transmission line could deliver the generated energy but face a loss of power along the transmission line, and the delivered energy is slightly below the expected threshold. In other research by [81][82], topology degeneration also induced expected energy not transmitted (EENT).…”
Section: Degradation Valuementioning
confidence: 99%
“…The deteriorations were similarly begun at the design and installation stage, where the network topology and grid architecture slightly affect the transmitted energy. It is found that several transmission disturbances were triggered by improper design of topology and architecture [81] [82]. A transmission line design without considering the surrounding environment was found with an unexpected nuisance, e.g., component corrosion [83], overloading load [83], out of range working frequency [84], or underrated coupling between grid networks [85].…”
Section: B System Deteriorationmentioning
confidence: 99%